Pigmented eccrine poroma on scalp simulating melanoma - Bruno de Oliveira Barbosa; Isabella Stamato Pimenta Barbosa (Revista Brasileira de Cirurgia Plástica)
Introduction: The eccrine poroma is a benign lesion, usually solitary and nodular, frequent in the palm and foot plant. Due to its rarity, the pigmented variant can easily be confused with melanoma. A clinical case of pigmented poroma on the scalp is reported; this is a location considered atypical, simulating malignant melanoma. Case Report: A 73-year-old male patient, phototype IV, reported the appearance of a painless lesion on the scalp for six months, associated with sporadic bleeding. On examination, it presented as a blackened nodule with an erythematous center of firm consistency, measuring approximately 1.5 cm in diameter. Dermatoscopy observed a predominant vascular pattern in blood cells. The main diagnostic hypothesis was melanoma, but the histopathological study concluded partially pigmented eccrine poroma. Discussion: Pigmented eccrine poroma is a rare tumor with unknown pathophysiology. It is considered a great simulator for clinically imitate several tumors, benign and malignant. In this clinical case, after dermatological examination and dermoscopic evaluation, the main diagnostic hypothesis was malignant melanoma. The few clinical cases published with a dermatoscopic study presented a similar history and diagnostic doubt, and the diagnosis was clarified only after histopathological evaluation. Conclusion: The evaluation of pigmented skin lesions must be done both clinically and with dermatoscopy, used as a tool that corroborates the diagnosis. The diagnostic hypothesis of eccrine poroma should be considered when pigmented lesions do not have melanocytic characteristics, and the diagnosis is confirmed only after histopathological evaluation.